1999
DOI: 10.1021/es980782k
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Alkylphenols in Fish Tissues, Sediments, and Waters from the U.K. Tyne and Tees Estuaries

Abstract: Nonylphenols and related compounds are common products of biodegradation of a large group of nonionic surfactants, the nonylphenol polyethoxylates. Many of these compounds are known to be environmentally persistent and to elicit estrogenic response in both mammals and fish. In this study, nonylphenol (NP), nonylphenol monoethoxylate (NP1EO), and octylphenol (OP) were found in tissues of mature male flounder, Platichthys flesus (5-55 ng/g NP, 190-940 ng/g NP1EO, wet weight), and in tissues of juvenile flounder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
2
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(104 citation statements)
references
References 39 publications
7
91
2
4
Order By: Relevance
“…Apparently the pollution levels of APs in the river sediments are higher in the PRD than in Korea, Germany, Spain, and Netherlands, while they are close to the concentration ranges in urban and industrial zones and their adjacent areas located in Japan, US, UK, and Canada. The BPA concentration ranges are also in the high value scope, and similar to those in Elbe River, Germany (Heemken et al, 2001), and Tyne and Tees estuaries, UK (Lye et al, 1999), and higher than those of the other investigated European rivers. The concentrations of natural estrogen E1 in the sediments of the PRD are at high levels as well, and similar to those in the Spanish rivers , and lower than those in Ouse River of UK, but higher than those in Japanese and the other investigated European rivers.…”
Section: Comparison With Other Areas In the Worldsupporting
confidence: 62%
“…Apparently the pollution levels of APs in the river sediments are higher in the PRD than in Korea, Germany, Spain, and Netherlands, while they are close to the concentration ranges in urban and industrial zones and their adjacent areas located in Japan, US, UK, and Canada. The BPA concentration ranges are also in the high value scope, and similar to those in Elbe River, Germany (Heemken et al, 2001), and Tyne and Tees estuaries, UK (Lye et al, 1999), and higher than those of the other investigated European rivers. The concentrations of natural estrogen E1 in the sediments of the PRD are at high levels as well, and similar to those in the Spanish rivers , and lower than those in Ouse River of UK, but higher than those in Japanese and the other investigated European rivers.…”
Section: Comparison With Other Areas In the Worldsupporting
confidence: 62%
“…Compared with the other aquatic surface sediments (Fig. 3), the concentrations of total APs in this study are generally higher than most of those reported for other areas of the world, and lower than those of the two samples in the Hamilton Harbor site, Canada [20][21][22][23][24][25][26][38][39][40][41][42][43][44][45]. High concentrations of APs were reported for other highly industrialized and urbanized areas, such as Hamilton Harbor of the Great Lakes (up to 72,000 ng/g dw of NP and 1800 ng/g dw of OP) [38], Virginia (USA) sediments adjacent to STPs and outfall (up to 14,100 ng/g dw) [23], and Jamaica Bay (NY, USA)(up to 13,700 ng/g dw of NP and 45 ng/g dw of OP) [25].…”
Section: Ap Contents By Soxhlet Extraction and Distributioncontrasting
confidence: 74%
“…Organic compounds reported to disrupt normal reproductive pathways in animals include pesticides, certain polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs), and alkylphenols (Miyamoto and Klein, 1998). With respect to the latter, 4-nonylphenol (4-NP) is of growing concern due to its estrogenic effects on aquatic organisms (Soto et al, 1991;Jobling and Sumpter, 1993;White et al, 1994) and its prevalence in the environment (Lye et al, 1999;Thiele et al, 1997). The residual 4-NP in the aqueous environment predominantly stems from the wide use of nonylphenol polyethoxylate (NPEOs) surfactants of various ethoxylate chain lengths.…”
Section: Introductionmentioning
confidence: 99%